(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
It is a great honor for me to welcome you to this important and inspiring event — the International Congress «Traditional Culture and Art: Problems of Preservation and Development,» which is taking place as part of the World Festival «Ruh Sanat.»